Prepayment, salience, and welfare - Imelda; Anna Lou Abatayo; Budy Resusodarmo (Graduate Institute of International and Development Studies, 2024)
The timing of payment can enhance salience, making customers more price-responsive when paying before consumption rather than after. This study examines Indonesia's nationwide switch to prepaid electricity metering, impacting over 40 million households. We find that prepaid metering users are twice as price-elastic as postpaid users. We also find a positive willingness to pay for prepaid metering, suggesting consumer welfare gains. As prices rise, prepaid metering reduces excess burden by 1.5% and CO2 emissions by nearly 6%. These findings suggest prepaid meters can support climate policy goals by promoting energy conservation without imposing significant burdens on consumers.
Keywords: Q41; Q48; I30; 330; electricity; prepayment; elasticity; salience; energy conservation